The minimum complexity necessary: The value of a simple Social-Ecological systems analysis in holistic marine environmental management - Gemma Smith; Jonathan Atkins; Amanda Gregory; Michael Elliott (Sustainable Futures)
The marine environment is a complex adaptive system, in which natural components interact with pressures from human activities and climate change. Effective marine management must navigate this complexity to protect biodiversity and ensure societal benefits. Increasingly, it is recognised that a functional, integrated approach is essential for sustainable management. This paper presents a comprehensive interrogation of nine existing Social-Ecological System (SES) frameworks, aiming to learn from these and identify the most suitable approach for managing the complex and adaptive nature of marine systems. Through a rigorous SWOT analysis and the application of appropriate characteristics criteria derived from the Ecosystem Approach principles, we evaluate various frameworks potential for operationalising ecosystem-based marine management. Key attributes such as holism, resilience, cross-scale interactions, stakeholder involvement, and adaptive learning emerge as critical to effective marine management. Our analysis reveals that while no single framework is perfect, the Integrated Systems Analysis (ISA) demonstrates the potential due to its holistic approach, explicit learning design, stakeholder inclusion, and proven application in marine and coastal contexts. Nonetheless, recognising ISA's limitations, we propose integrating elements from other frameworks and Systems Thinking tools to create a refined, practical approach termed ‘Simple SES.’ The resulting ‘Simple SES’ aims to provide a tailored, yet manageable approach for practitioners, deciphering the complexity of marine systems and supporting well-informed decision-making. This work advances SES theory and practice, developing an operationalised framework that aligns with the goals of sustainable and successful marine management thereby making ecosystem-based management more achievable and integrative by applying a systems approach.